A review of iPhone and Android apps for cancer patients and survivors: assessing their quality, nutrition information and behaviour change techniques. Issue 3 (16th January 2021) - Keaver, Laura; Loftus, Amy; Quinn, Laoise
Abstract: Background: The present study reviewed the quality, nutrition content and behaviour change techniques (BCTs) of apps aimed at those with cancer. Methods: The Apple App Store and Androids' Google Play were searched in March 2020. Apps were scored for accountability as per Silberg's standards, quality as per the Mobile Application Rating Scale, and BCTs using the CALO‐RE Taxonomy. Nutrition content was summarised and a checklist developed from the European Society for Parenteral and Enteral Nutrition (ESPEN) cancer and nutrition guidelines and the World Cancer Research Fund (WCRF) guidelines for Cancer Survivors. Results: Twelve apps were identified, mean (SD) accountability score was 2.7/8 (2.0) (range 0–6) and quality score was 2.9/5 (0.6) (range 1.7–3.7). Overall, 11 BCTs were used (range 0–8 per app). Nutrition content focussed on healthy eating and meeting energy needs. There was a lack of strategies for implementation and no indication of whether the advice was more suited for specific cancer types, stages or treatment. Limited reference was made to recommendations of ESPEN and the WCRF. A strong positive relationship between quality and number of BCTs was found ( r  = 0.805, n  = 9, P  = 0.01). Conclusions: Little nutrition information is currently included on publicly available apps aimed at those with a cancer diagnosis. Abstract : An outline of the main messages of a review of iPhone and Android apps for cancer patients and survivors